EFFECT OF NATURAL SUCKLING ON POSTPARTUM REPRODUCTIVE PERFORMANCE OF NUBIAN GOATS - Abdel Wahid Salim, Hassna; E, A .; Ahmed Nour, Abu Nikhaila; M, A; A. E, Khalid (Journal of Veterinary Medicine and Animal Production, 2022)
This study was conducted to investigate the effect of natural suckling on reproductive performance of Nubian Goats. The study involved 20 multiparous Nubian goats allocated randomly according to body weight and age to two equal groups of 10 does each. Group A suckled their kids for 13 weeks while group B (control) kids were reared artificially by bottle for 13 weeks. The results showed that the mean postpartum anoestrus interval (PPAI) length was 57.8±21.5 days compared to 20.4± 4.4 days in the two groups respectively. The results indicated a high significant difference (P<0.001) in favor of the suckled group. The duration of oestrus in group A was shorter than that in group B with values of 29.89± 3.04 versus 31.89 ± 6.42 hrs, respectively. The gestation length in the two groups was 152.3 ± 5.4 and 151 ± 3.9 days. The litter size in the two groups was similar 1.75 ± 0.71 and 1.7 ± 0.5. The kidding interval was highly significantly (P<0.001) affected by the treatment. The recorded values were 210.1± 25.6 versus 171.4 ± 7.2 days for group A and B, respectively. The Hassna. A.E. el al.